Menyoal Pengaturan Fleksibilitas Hubungan Kerja di Indonesia: Perspektif Undang-Undang Cipta Kerja - Dananjaya, Nyoman Satyayudha (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aimed to analyze the arrangement of flexible labor relations before and after the passing of the copyright work law, the influence of the arrangement of flexible labor relations on the legal protection of workers’ rights, as well as the ideal arrangement of labor relations in the future in protecting workers’ rights. This study used normative juridical, historical, statutory, and conceptual methods. Data collection techniques were obtained from primary, secondary, and tertiary legal materials. The data obtained were analyzed using descriptive analytical techniques. The results of the study showed that the arrangements in the labor law after the enactment of the work copyright law had undergone many changes, namely the validity period of work agreements for a particular time which was extended in Government Regulation Number 35 of 2021, and the expansion of the scope of outsourcing. The regulation of the flexibility of labor relations affected the guarantee of workers’ rights to obtain job security and welfare as mandated in the constitution. Strengthening the government’s position in industrial relations and repositioning the position of workers juridically and sociologically was needed to regulate flexible labor relations to guarantee workers’ rights in the future.